Tracing and tracking printmaking exhibitions in Malaysia: 1960-2020 / Mohd Jamil Mat Isa - Mat Isa, Mohd Jamil (Universiti Teknologi MARA, Perak, 2023)
Historical records prove that printmaking was a medium of communication in various civilizations in Egypt, Japan, and Europe before it was elevated as one of the disciplines of painting. Penang was a popular location for this creative industry sector in the early stages. This study looks chronologically as much as possible at the organization of printmaking exhibitions in Malaysia from the 1960s until 2000. The activities organized by private art galleries play a significant role in the career of artists. The objective of this study is to chronologically document the organization of printmaking exhibitions by the National Art Gallery, private art galleries, and artist groups. Data collection methods through various gallery publication materials have been carried out to complete this study.